Effect of effective microorganism (EM) on the nutritive quality of Napier silage - Othman, Hafis (2016)
Famers nowadays, are concern on the purpose of making silage to preserve the supply of feedstuff to the livestock for a long a period of time. This study was conducted to determine the nutritive value and the dry matter content of Napier silage inoculated with commercial EM. The Napier grass were cut back and fertilized at Ladang 2 and harvested randomly at 6 week of age. The Napier had been ensiled and divided into 3 different treatments. The treatment involved were Napier with water for treatment 1, Napier only for treatment 2 and Napier with EM for treatment 3 with total 15 containers where the containers were opened at five different time interval. The laboratory analysis were conducted at Nutrition Laboratory Animal Science Department to analyze for dry matter (DM), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), and acid detergent lignin (ADL). pH value of the silage was also measured. There was significant difference (P<0.05) observed in DM and NDF value when analyzed on same treatment with different periods of time. For DM, treatment 3 showed the highest percentage of DM (76.35%) compared to other treatment. Treatment 1 was significant compared to treatment 2 and treatment 3 in NDF. Meanwhile, there was no significant difference on CP, ADF and ADL. For the pH reading at time interval of 4 days, treatment 2 showed significant difference (P<0.05) compared to treatment 1 and treatment 3. There was no significant difference during the periods of 8, 12, 16 and 20 days when pH readings were compared to other treatment. For the aerobic stability, it was shown that the pH of the inoculated Napier silage was more stable after a few openings compared to other treatment. In conclusion, the Napier silage treated with EM slightly increased the nutritive value contents of the silage. Better understanding in the uses of EM inoculants in the silage encourage farmer to use it as an additive that will improves silage quality.